Peningkatan Keterampilan Membaca Lancar menggunakan Model Oral Reading Fluency di Kelas II SDN 20 Berok Gunung Pangilun Kota Padang - Sari, Trisna Adita; Suriani, Ari; Meizatri, Ranti; Sukma, Elfia (Lembaga Yasin AlSys, 2025)
The low oral reading fluency skills among second-grade students at SDN 20 Berok Gunung Pangilun, Padang City. Initial observations revealed that most students read haltingly, neglected punctuation, and struggled with unfamiliar vocabulary; only 9 out of 24 students met the minimum mastery criteria. This study aims to improve oral reading fluency skills through the implementation of the Oral Reading Fluency (ORF) model. The research employed Classroom Action Research (CAR) with both qualitative and quantitative approaches, conducted in two cycles. The subjects included the classroom teacher as observer, the researcher as practitioner, and 24 students as research participants. Data were collected through observation, tests, and interviews. The findings indicate significant improvements in three key areas: lesson planning increased from 83.3% to 91.6%; teacher activity from 85.65% to 92.8%; and student activity from 67.85% to 82.1%. The average score for reading skills rose from 65.75 to 85.5, while the fluent reading evaluation score increased from 58.95 to 82.6. The combined average for oral reading fluency skills reached 84.05. These results demonstrate that the ORF model is effective in enhancing oral reading fluency among second-grade students and can serve as an alternative instructional strategy to improve basic literacy skills in elementary education.